2010
DOI: 10.1093/aob/mcq017
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the role of heat and smoke as germination cues in Mediterranean Basin flora

Abstract: The results suggest that both heat and smoke are important germination cues in a wide range of MB woody species and that fire-cued germination in woody plants of the MB may be as important as in other MTEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
198
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(216 citation statements)
references
References 44 publications
10
198
1
7
Order By: Relevance
“…Keeley et al 2011). Several species from Mediterranean ecosystems show fire-related cues to germi- nation (see Moreira et al 2010), being fire-dependent, while other species can germinate after temperature fluctuations (gap-dependent, Ooi et al 2014). Our study showed that only seeds of Stylosanthes montevidensis had a fire-related increase in germination after the exposure to 120ºC, showing breakage of physical dormancy of at least 20% of the seeds.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Keeley et al 2011). Several species from Mediterranean ecosystems show fire-related cues to germi- nation (see Moreira et al 2010), being fire-dependent, while other species can germinate after temperature fluctuations (gap-dependent, Ooi et al 2014). Our study showed that only seeds of Stylosanthes montevidensis had a fire-related increase in germination after the exposure to 120ºC, showing breakage of physical dormancy of at least 20% of the seeds.…”
mentioning
confidence: 54%
“…Fire-related germination is found in different types of vegetation, but most studies describe this relationship in Mediterranean ecosystems (see Reyes & Trabaud 2009;Moreira et al 2010) and in Australia (see Auld & O'Connell 1991;Ooi et al 2014). Keeley et al (2011) concluded thus, that breaking the dormancy or stimulating the germination by fire cues should be considered as evidence for selective pressures in plant evolution.…”
mentioning
confidence: 99%
“…Temperatures reached during the passage of fire can break physical dormancy of hard-coated seeds, allowing subsequent water imbibition and germination when environmental conditions are suitable (Auld and O'Connell 1991;Keeley 1991;Cocks and Stock 1997;Bell 1999). In addition, smoke can also affect the physiology of seeds and directly stimulate germination (Brown 1993;Dixon et al 1995;Keeley and Fotheringham 1998;Van Staden et al 2000;Moreira et al 2010) or act in combination with heat (Keeley 1991;Keith 1997;Morris 2000;Thomas et al 2003). Other direct fire cues, such as charred wood, can also act to stimulate seed germination in some species (Keeley 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Heat shock and chemicals derived from smoke, ashes or charred wood are the cues often proposed by ecologists to test and illus-trate fire-stimulated germination (e.g. Keeley, 1987;Moreira et al, 2010;Thomas et al, 2010). Fire-cued germination has been considered to be adaptive in fire-prone environments, since it makes seedling emergence coincide with temporary favourable conditions, where light and soil nutrients increase and negative biotic interactions (e.g.…”
Section: Introductionmentioning
confidence: 99%